Pengaruh Fasilitas dan Media Promosi terhadap Keputusan Berkunjung Kembali di Wisata Alam Geosite Sipinsur Kabupaten Humbang Hasundutan - Purba, Tuti Damayanti; Simbolon, Anggiat Parlindungan (BUDGETING : Journal of Business, Management and Accounting, 2024)
The Sipinsur Geosite is a tourist attraction in Humbang Hasundutan Regency which is often visited by tourists with its beautiful natural views of Lake Toba. There are several factors that influence the decision to return to a destination such as facilities and promotional media. This research aims to determine the influence of facilities and promotional media on the decision to return to the Sipinsur Geosite partially and simultaneously. This research was conducted using a quantitative approach. The object of this research is the Sipinsur Geosite with data collected through a questionnaire. Analyzed using data quality tests, classic assumption tests consisting of normality and reliability, multiple linear analysis, hypothesis testing and coefficient of determination tests. The results of the research show that facilities and promotional media partially have a positive and significant influence on the decision to revisit the Sipinsur geosite natural tourist attraction with a calculated t value for facilities of 2.752 and promotional media of 9.639. Simultaneously, facilities and promotional media have a positive and significant influence on the decision to visit again with a value of f count > f table 96.101> 3.091 and overall facilities and promotional media influence interest in visiting again by 66.5% and the remaining 33.5% is influenced by factors. other. Keywords: Facilities, Media Promotion, Visit Decision